Addressing Equity in Academic Integrity - Steeves, Marcia (Canadian Perspectives on Academic Integrity, 2024)
This literature review examines equity issues within academic integrity systems in higher education and explores strategies for fostering an anti-racist and equitable approach to academic integrity practice. The study acknowledges that existing academic integrity policies and practices in Canadian higher education are rooted in white-dominant ideologies propagated by colonial history, leading to a number of barriers for marginalized and racialized students. The research question of this study focuses on identifying equity barriers present in academic integrity systems and exploring existing equity practices applicable to academic integrity policy and practice to address barriers. A qualitative review of relevant literature (n = 27) was conducted, utilizing tertiary and secondary sources, and institutional databases. The findings reveal three key equity barriers prevalent in the literature: ways of knowing and belonging, language use, and citations and attribution systems. The study also identifies seven equity strategies from the literature and proposes specific application of these across policy development, academic integrity practice, teaching practice and advocacy work. In conclusion, the literature review highlights the need to address systemic barriers in academic integrity and emphasizes the importance of anti-racist and equitable approaches. By implementing strategies that promote inclusivity, cultural responsiveness, and recognition of diverse knowledge systems, higher education institutions can foster a more equitable academic environment. The review provides relevant recommendations for discussion and advocacy among scholars and academic integrity practitioners.